Analysis of Factors Related to Midwife's Performance in Filling the "Poedji Rohyati" Score in Early Detection of High Risk Pregnancy atPublic Health Center of Lima Puluh Kota District - Liza Andriani; Yuniar Lestari; Erwani Erwani (Journal of Midwifery, 2018)
One indicator that determines community health status is mortality. Midwives as the spearhead of antenatal care must be able to prevent maternal mortality rates (AKI) by increasing their performance in providing antenatal services in accordance with standards. One attempt to prevent AKI is by early detection of high-risk pregnancy using the PoedjiRohyati score card (KSPR). Midwife's performance is influenced by several factors, namely individual, organizational and psychological factors. This study aims to analyze the factors related to the performance of midwives in filling the PoedjiRohyati score card on early detection of high-risk pregnancies in the Lima Puluh Kota District Health Center.       This study uses a combination of quantitative and qualitative methods. Quantitative research samples were 74 respondents, data collection was carried out from January to February 2018 with interview techniques using questionnaires and observation sheets. While the qualitative research informants were the Head of Community Health and Nutrition, the head of the puskesmas and the midwife coordinator of the Piladang, Taram, Koto BaruSimalanggang and TanjungPati health centers.       The results of the study prove that the factors associated with the performance of midwives in filling in the KSPR include the level of knowledge (p = 0.031), attitude (p = 0.004), motivation (p = 0.020) and supervision (p = 0.025). The factors that are most related to the performance of midwives in filling in KSPR are attitudes (p = 0.006).      Based on the research, it can be concluded that the midwife will have a good performance in filling in the KSPR if it is based on a high level of knowledge, a positive attitude, high motivation, periodic supervision and supported by complete facilities.